Leucospis leucotelus (Hymenoptera: Leucospidae) as a parasitoid of the large carpenter bee X ylocopa lateralis (Hymenoptera: Apidae, Xylocopinae) in Colombia - Lucia, Mariano (2019)
We report Leucospis leucotelus Walker parasitizing nests of Xylocopa(Schonnherria) lateralis Say in Colombia. Previous literature records of species of Leucospisassociated with species ofXylocopa are summarized.